A Comparative Study of Effect of Solvents on Relative Viscosities of Some Substituted Benzo-1,2,5-Thiadiazines - P. Deohate, Pradip; B. Agrawal, Pratibha; Berad, B.N. (Asian Journal of Chemistry, 2010)
The viscosities and densities of benzo-(3,4-c)-6-phenylimino-1,2,5- thiadiazine (I), benzo(3,4-c)-6-o-tolylimino-1,2,5-thiadiazine (II), benzo( 3,4-c)-6-m-tolylimino-1,2,5-thiadiazine (III), benzo-(3,4-c)-6-p-tolylimino- 1,2,5-thiadiazine (IV) , benzo-(3,4-c)-6-o-chlorophenylimino-1,2,5- thiadiazine (V), benzo-(3,4-c)-6-p-chlorophenylimino-1,2,5-thiadiazine (VI) and benzo-(3,4-c)-6-t-butylimino-1,2,5-thiadiazine (VII) in different percentages of acetone-water, ethanol-water and dioxane-water mixtures have been measured. From the data the relative viscosities have been calculated which are used to measure the molecular interactions in the solutions and to compare the viscosity behaviour of substituted benzo- 1,2,5-thiadiazines on the basis of presence of different substituents.